The role of results-based strategic planning in financing small projects to increase production -A field study on financial institutions and owners of small projects- - Salih, Huda Diyab Ahmed; Hamza, Randa Abd Elhamied Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aims to light on the results-based strategic planning for financing small projects and its role in increasing production and productivity from the perspectives of financial institutions and owners of small projects through studying the hypotheses that First hypothesis: There is a statistically significant relationship between results-based strategic planning in financing small projects and increasing production and productivity from the point of view of financing institutions in Sudan. Second hypothesis: There is a statistically significant relationship between results-based strategic planning in financing small projects and increasing production and productivity from the perspective of small business owners in Sudan. To study the hypotheses and achieve the objectives of the research, the inductive, deductive and historical approach was followed, and the questionnaire tool was used to collect data, and the analysis was done using the Statistical Packages Program (SPSS) to analyze the search hypotheses phrases using the frequency table and the arithmetic mean to show the differences in the answers of the research sample. From the financial institutions and owners of small projects, the research reached a set of results, including: The financing of small projects from the perspectives of financial institutions and owners of small projects is carried out according to strategic planning based on results in Sudan to ratio (%80). The research also recommended many recommendations, including: A lot of research and studies should be done in strategic planning based on results.
Keywords: financing; small projects; production and productivity; strategic planning